(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article discusses the results of research on the development of the chemical composition and mechanical properties of reinforcement No. 12 made of steel grade 22C, as well as the development of a technology for obtaining thermomechanically hardened coiled rebar. It is shown that the proposed profile provides better hardenability of the rolled section and increases the efficiency of water cooling. The best results in terms of mechanical properties were obtained for rolled products made of steel grade 460B. A method of hot rolling of steel and a method of production of reinforcing bars of increased strength are proposed, one of the important components of which is microalloyed vanadium in the range of 0.04-0.10%, which will ensure an increase in the strength level up to 30%. The results of mechanical tests of coiled reinforcing bars and comparative data on the mechanical properties of reinforcement No. 12 rolled on mill 320 are also presented. It is shown that the use of steel microalloyed with vanadium makes it possible to obtain reinforcing bars with an effective profile with a nominal diameter of 5.5—8.0 mm, class A500C, in a temperature range acceptable for the equipment of mill 150.